2009
DOI: 10.1029/2009gc002440
|View full text |Cite
|
Sign up to set email alerts
|

NA‐SWS‐1.1: A uniform database of teleseismic shear wave splitting measurements for North America

Abstract: [1] This version of shear wave splitting (SWS) database (DB) for North America (NA) contains 6224 pairs of splitting parameters (fast polarization directions and splitting times) measured using all the available data recorded by digital broadband seismic stations over the period of 1980-2007 and archived at the Incorporated Research Institutions for Seismology Data Management Center. The measurements were produced using a set of robust procedures that involve automated batch processing and manual screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 30 publications
8
51
0
Order By: Relevance
“…This study also uses the SC method to analyze more data and thereby to enhance the reliability of results. The calculation methods, data selection, classification and analysis techniques applied here are in accordance with Liu et al [14]; more details and examples can be found elsewhere [31,32].…”
Section: Methodsmentioning
confidence: 91%
“…This study also uses the SC method to analyze more data and thereby to enhance the reliability of results. The calculation methods, data selection, classification and analysis techniques applied here are in accordance with Liu et al [14]; more details and examples can be found elsewhere [31,32].…”
Section: Methodsmentioning
confidence: 91%
“…Manual checking was applied to each of the measurements. During the manual checking stage, the start and end times of the XKS window, the band-pass filtering parameters, and results of automatic ranking were visually verified, and adjusted if necessary to ensure reliable results (Liu, 2009). …”
Section: Xks Splittingmentioning
confidence: 99%
“…The seismograms were band-pass filtered with corner frequencies of 0.04 and 0.5 Hz which is the main frequency band of the XKS phases. Those with a signal to noise ratio (SNR) lower than 4.0 on the original radial component were not used for SWS analysis (see Liu and Gao, 2013 for the specific definition of the SNR).…”
Section: Xks Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Savage and Silver 1993;Herquel et al 1999;Savage 1999;Rümpker et al 2003;Roy et al 2007), and observations of older crust and mantle lithosphere show "fossil" anisotropy (Babuška and Plomerová 2006). A recent compilation of data for seismic anisotropy in North America (Liu 2009) shows that most fast directions in shear-wave splitting are parallel with the modern direction of absolute plate motion, indicating that the source of the anisotropy is in the asthenosphere. Some sites of seismic anisotropy, however, have fast directions that are not parallel with absolute plate motion, suggesting that the source of the anisotropy may be in the mantle lithosphere.…”
Section: Discussionmentioning
confidence: 99%